Thiết kế kế hoạch bài dạy tích hợp tiếng Anh trong dạy học môn Toán ở tiểu học - Phan Thị Hồng The, Phan Thị Hồng The; Trịnh Thị, Hiệp (Tạp chí Giáo dục, 2026)
Integrating English into the teaching of Mathematics in primary school contributes to the simultaneous development of mathematical and language skills for students in the context of current educational reform and international integration. However, this is a new approach, lacking practical evidence and specific lesson design guidelines for primary school teachers. This article uses theoretical research methods, document analysis, and illustrative lesson design to propose a process for designing lesson plans integrating English into Mathematics in primary school. The process consists of 5 steps: (1) Identifying the learning objectives; (2) Identifying tools, means, and designing teaching materials; (3) Designing teaching activities; (4) Designing assessment; (5) Adjusting the lesson plan. Based on this, the proposed process is illustrated through the design of several specific lesson plans. The research results show that the proposed process provides clearer guidance for teachers in designing integrated lessons, ensuring a balance between mathematics education goals and English language development goals, while also enhancing opportunities for students to use English in learning mathematics. This paper contributes to providing a reference basis for developing integrated lessons in elementary mathematics with an approach that incorporates English content and language.